Faktor-Faktor yang Berhubungan dengan Tingkat Capaian Pemberian Obat Cacing di Gampong Gajah Ayee Kecamatan Pidie Kabupaten Pidie - Razi, T. Khairol; Wahidanur; Syamsuddin; Jannah, Raudhatul; Syahputra, Fadli (Sagita Academia Journal, 2025)
Worm diseases are often found in areas with high humidity, especially in community groups with poor personal hygiene and environmental sanitation. Worm infections frequently affect elementary school-age children because they are usually in contact with soil. Worm worms are transmitted through dirty hands and long and dirty nails, causing worm eggs to be deposited. One of the causes of the spread of worms is poor personal hygiene. This research aimed to determine the factors related to the level of achievement of giving worm medicine to children at SDN 4 Pidie, Pidie District. This research is analytical and has a cross-sectional study design. The population and sample for this research were 61 students at SDN 4 Pidie. This research was conducted on 15-19 July 2024. The sampling technique was Accidental Sampling. Data collection was carried out using a questionnaire. The results of the bivariate test showed that there was a relationship between knowledge and the level of achievement of giving worm medicine to children at SDN 4 Pidie, Pidie District (p-value = 0.001), there was a relationship between education and the level of achievement of giving worm medicine to children at SDN 4 Pidie, Pidie District (p-value = 0.000), and there is a relationship between the role of the teacher and the level of achievement of giving worm medicine to children at SDN 4 Pidie, Pidie District (p-value = 0.001). It is recommended that parents maintain environmental sanitation and further improve children's personal hygiene to avoid infection with soil Transmitted Helminths (STH) intestinal nematode eggs.